The effectiveness of problem-based learning on reading comprehension of eleventh-grade science students at SMAN 1 Sambit - Muhsyanura, Intan; Kirana, Dhinuk Puspita (Labschool Cibubur, 2024)
Reading is one of the most important basic skills in learning English for students to learn. Reading is understanding written text which is a complex activity involving perception and thinking which consists of two processes related to word recognition and understanding. Comprehension is the process of understanding interconnected words, sentences and texts. Therefore, reading cannot be separated from understanding. The purpose of this research is to find out whether there is a significant difference between students who are taught using problem-based learning and have better reading comprehension than students who are not taught using problem-based learning. Researchers applied a quantitative research approach with quasi-experimental design. This research used two classes. The population in this study were all XI Science students at SMAN 1 Sambit, totaling 87 students. The sample in this study was an experimental class with 29 students and a control class with 29 students. Researchers used pre-test and post-test in data collection. Data were analyzed using a t-test formula such as the Independent Sample T-Test. The results showed that the mean post-test for experimental class was 89.82 and the mean post-test for control class was 80.93. This shows that there is a difference in mean scores between the two classes. The T-Test results show a significance value of 0.00 which is smaller than 0.05. Based on these data, it can be concluded that there is a significant difference between reading comprehension of students who are taught using problem-based learning than students who are not taught using problem-based learning.